Larutan Pulsing dengan Penambahan Gula dan Asam Salisilat Mempertahankan kesegaran dan Kualitas Bunga Matahari Potong: Pulsing Solution with Added Sugar and Salicylic Acid Maintains Freshness and Quality of Cut Sunflowers - Dewi Sukma; Amarillis, Shandra; Abdullah Bin Arif (Jurnal Hortikultura Indonesia, 2022)
Sunflower is an important ornamental plant based on economics. The cut sunflowers require proper postharvest handling to maintain quality and extend the freshness of flowers during marketing and transportation. One technology that can overcome this problem is applying a pulsing solution. This study aimed to determine the best pulsing solution to maintain cut sunflowers’ freshness and quality. The experimental design used in this study was a completely randomized design (CRD). The pulsing solution consisted of a mixture of distilled water, sugar, salicylic acid, and sodium hypochlorite (5.25%). The observation parameters included: flower diameter (outside and inside), number of withered flower petals, number of flower petals with spots, number of fresh flower petals, and measuring the decrease in the volume of distilled water from each bottle. The observations were made at the beginning before and every two days after the storage period. The results showed that the pulsing solution treatment containing distilled water + 3% sugar + sodium hypochlorite 0.25% + 75 ppm salicylic acid tends to be more effective in water absorption so that it can maintain the freshness and quality of cut sunflowers for up to 6 days after harvesting. Keywords: cut flowers, pulsing solution, sunflower